RETRACTED: An ontological approach to the methodology of vintage analysis in the diagnosis of sustainable development of the region - Mushketova Natalia; Zudina Elena; Skiter Natalia; Boriskina Tatyana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001